A method for anti-ransomware testing based on reinforcement learning - Бен Гуррам Мохамед Тайеб (My University, 2022)
In this document, we will run experiments to explore some future techniques that black hat hackers could use in the future to bypass anti ransomware protection, it is very important to predict and defend against such techniques before a real-world attack happens. Since ransomware attacks are very criticial especially that companies got very important documents encrypted, and it is worse if they don’t have backups, individuals lose in most cases important personal files, and in most cases, they don’t have backups
Keywords: штучний інтелект; машинне навчання; DQN; DQL; QL